Swimming turn technique optimisation by real-time measurement of foot pressure and position - Chakravorti, N.; Slawson, S. E.; Cossor, J.; Conway, P. P.; West, A. A. (Procedia Engineering, 2012)
The objective of the research outlined in this paper is to provide real-time quantifiable measures of individual foot positioning and force exerted during the tumble turn, as opposed to the single contact point of the currently employed force plate systems [1]. A thin film pressure sensor has been employed to measure pressure exerted on the wall during the turn. Real-time automated image processing algorithms have been developed to measure a swimmer's performance for tumble turns. The algorithms yield performance parameters including contact time, foot orientation, distance between feet, lane position, depth of contact with the pool wall and the perpendicular force exerted per foot during the turn. The system significantly improves the efficiency of the analysis process and provides real-time feedback to the coaches, sports scientists and athletes.